2015
DOI: 10.1016/j.pmrj.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Leg Squat Performance is Impaired 1 to 2 Years After Hip Arthroscopy

Abstract: Single leg squat performance is impaired one to two years after hip arthroscopy ABSTRACT 1 2 Objective: 1. Evaluate single leg squat performance 1-2 years after arthroscopy for intra-3 articular hip pathology, compared to controls and the non-operative limb. 2. Investigate 4 whether single leg squat performance on the operated limb was associated with hip muscle 5 strength. 6Design: Cross-sectional study 7Setting: Private physiotherapy clinic and university laboratory. 8Participants: Thirty-four participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 35 publications
4
34
0
1
Order By: Relevance
“…A lack of consistency in the control groups makes it difficult to have confidence in the validity of between-group differences reported. These findings are similar to those in a recent study by Charlton et al 59 that reported patients' posthip arthroscopy having increased frontal plane hip adduction and knee valgus compared with controls. The authors suggested that this may perpetuate impingement load in the hip during single leg functional tasks and called for targeted rehabilitation programmes to improve lower limb control during these tasks 59.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A lack of consistency in the control groups makes it difficult to have confidence in the validity of between-group differences reported. These findings are similar to those in a recent study by Charlton et al 59 that reported patients' posthip arthroscopy having increased frontal plane hip adduction and knee valgus compared with controls. The authors suggested that this may perpetuate impingement load in the hip during single leg functional tasks and called for targeted rehabilitation programmes to improve lower limb control during these tasks 59.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are similar to those in a recent study by Charlton et al 59 that reported patients' posthip arthroscopy having increased frontal plane hip adduction and knee valgus compared with controls. The authors suggested that this may perpetuate impingement load in the hip during single leg functional tasks and called for targeted rehabilitation programmes to improve lower limb control during these tasks 59. Biomechanically, some studies suggest that symptomatic FAI affects walking by reducing speed60 and limiting ROM in the sagittal and frontal planes46 60 61 as well as reducing peak hip extension, abduction,46 61 adduction and internal rotation during the stance phase of gait 60.…”
Section: Discussionsupporting
confidence: 92%
“…The authors suggested that this may perpetuate impingement load in the hip during single leg functional tasks and called for targeted rehabilitation programmes to improve lower limb control during these tasks. 59 Biomechanically, some studies suggest that symptomatic FAI affects walking by reducing speed 60 and limiting ROM in the sagittal and frontal planes 46 60 61 as well as reducing peak hip extension, abduction, 46 61 adduction and internal rotation during the stance phase of gait. 60 These findings contradict the conclusions of this review where no significant difference was noted in ROM between individuals with symptomatic FAI and normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Since completion of this study, further evidence has been published reporting specific muscle weakness in subjects with labral pathology [27], in FAI [31] and post-hip arthroscopy [32]. Recommendations as a result of these studies have been made to target single leg squats [32] and hip flexor strength in rehabilitation [2]. Our study demonstrated statistical significance regarding the positive benefits of pre-operative exercise in these two muscle groups, with the intervention group performing better in strength (hip flexion P  = 0.02 and knee extension/quadriceps P  = 0.05).…”
Section: Discussionmentioning
confidence: 99%